Implementasi Model Pembelajaran Make A Match untuk Meningkatkan Minat Belajar dan Hasil Belajar Siswa Pada Mata Pelajaran IPS di SDN Grudo III Ngawi - Sandy, Deviana Putri Ari; Mala, Asnal (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Research on the application of the make a match learning model was carried out to increase student interest in learning and learning outcomes. The research methodology used is quantitative research. Researchers used a pre-experimental design method with a One Group Pretest-Posttest Design research design. The research subject is the fifth grade of elementary school. Meanwhile, the sampling technique used 24 students in one class. With the results of the research that has been carried out, there is agreement in the class that the average achieved before using the make a match type cooperative learning model shows a pre-test score with an average of 70.83 and after applying this learning model, the post-test shows the pre-test score. -test with an average of 70.83. The trial obtained an average score of 90. The conclusion was that this make a match type cooperative learning model had an effect on the interest in learning and learning outcomes of class V students at SDN Grudo III Ngawi